The Hadith on Ḥusn al-Ẓan as a Basis for Psychological Intervention to Reduce Overthinking in Adolescents - Muhammad Syarbini; Mustahkina Arsabandi; Junaidi Pohan (Yayasan Albahriah Jamiah Indonesia, 2025)
The phenomenon of overthinking in adolescents shows a significant increase, as indicated by a UNICEF report that noted an increase in anxiety symptoms in the 15–19 age group, primarily triggered by academic pressure, intense digital media use, and emotional instability during developmental transitions. This condition requires interventions that are not only cognitive but also rooted in values that can shape a more in-depth adaptive perspective. This study aims to describe the formulation of the concept of ḥusn al-Ẓan in primary hadith sources according to authenticity criteria and to design a conceptually relevant cognitive–spiritual intervention model to reduce adolescents’ tendency toward overthinking. The research method uses a qualitative-descriptive approach, tracing hadith from the Kutub al-Tisʻah, applying thematic analysis, and then mapping them against modern psychological frameworks, specifically cognitive reframing, emotional regulation, and positive attribution. The results show that ḥusn al-Ẓan provides a systematic cognitive restructuring framework through strengthening adaptive beliefs, reducing negative bias, increasing tolerance for uncertainty, and forming positive attributions towards oneself, situations, and others. These findings yield an intervention model that includes identifying maladaptive thought patterns, internalizing the principle of ḥusn al-Ẓan based on hadith texts, guided reflective practice, and positive reinterpretation strategies. Conceptually, this model has the potential to reduce rumination frequency, improve emotional regulation, and strengthen mental resilience in adolescents. Although not yet empirically tested, this model offers a robust conceptual foundation for developing preventive interventions rooted in Islamic values and encourages further research through quasi-experimental testing.